2017
DOI: 10.1002/ab.21740
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the use of corporal punishment: Child aggression, parent religiosity, and the BDNF gene

Abstract: Corporal punishment (CP) has been associated with deleterious child outcomes, highlighting the importance of understanding its underpinnings. Although several factors have been linked with parents' CP use, genetic influences on CP have rarely been studied, and an integrative view examining the interplay between different predictors of CP is missing. We focused on the separate and joint effects of religiosity, child aggression, parent's gender, and a valine (Val) to methionine (Met) substitution in the brain-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 64 publications
0
11
0
1
Order By: Relevance
“…For example, in a sample of Chinese adolescents, prosocial behavior toward strangers predicted greater paternal psychological control a year later (Fu & Zhang, 2020). Moreover, children's aggressive behavior predicted greater guilt induction from mothers of Chinese American preschoolers (Yu et al, 2019), and greater use of physical discipline among religious, but not secular, Jewish Israeli fathers (Avinun et al, 2018). Parent effects of psychological control on subsequent prosociality have also been observed (e.g., Fu & Zhang, 2020).…”
Section: Gen Er a L Discussionmentioning
confidence: 98%
“…For example, in a sample of Chinese adolescents, prosocial behavior toward strangers predicted greater paternal psychological control a year later (Fu & Zhang, 2020). Moreover, children's aggressive behavior predicted greater guilt induction from mothers of Chinese American preschoolers (Yu et al, 2019), and greater use of physical discipline among religious, but not secular, Jewish Israeli fathers (Avinun et al, 2018). Parent effects of psychological control on subsequent prosociality have also been observed (e.g., Fu & Zhang, 2020).…”
Section: Gen Er a L Discussionmentioning
confidence: 98%
“…3b). The use of corporal punishment by parents has been associated with depression, aggression, delinquent and antisocial behavior, and alcohol abuse in children (Gershoff, 2002), and studies have shown that it is affected by children’s genetically influenced tendencies; that is, evocative rGE processes are at play (Avinun, Davidov, Mankuta, & Knafo-Noam, 2018; Jaffee et al, 2004). Specifically, parents may use corporal punishment more with more aggressive children (Jaffee et al, 2004).…”
Section: Rgets May Be Widespreadmentioning
confidence: 99%
“…For example, the environment can moderate rGEs. A child’s aggressive behavior may evoke the use of corporal punishment by parents, but whether or not it will do so depends on context, such as culture (Avinun et al, 2018). Genetic correlations between phenotypes can also be moderated by the environment.…”
Section: The Complexity Of Human Behaviormentioning
confidence: 99%
“…Finally, to add to the complexity of the parenting-genes-child behavior network, two reports from LIST found that fathers' (but not mothers') parenting was predicted by an interaction between the val-met polymorphism in the BDNF gene and children's prosocial or aggressive behavior. The importance of children's behavior was exemplified by within-family twin comparisons such that Met carrier fathers differentiated more strongly between their children based on the child's behaviors (Avinun & Knafo-Noam, 2017;Avinun et al, 2018).…”
Section: Gene-environment Correlationsmentioning
confidence: 99%